The Brazilian Press and the environmental issues at the beginning of the XXI century: the amazon deforestation in journalistic discourse - Miranda Costa, Luciana (Revista General de Información y Documentación, 2016)
This article presents the main conclusions of a research that analyzed the intensification of environmental subjects in the news of the Brazilian Press during 2000-2006. The purpose was to examine how the journalistic discourse was structured at the beginning of the decade through its sources of information. The emphasis was on deforestation and forest fires in the Brazilian Amazon and subthemes related to them. In addition, the article aimed to identify the different discursive formations that based the media discourse. The main database was obtained through selection and analysis of 1096 articles published in major magazines and newspapers in Brazil. Most of the journalistic texts can be characterized as superficial, marked by a tone of "environmental alert" without explaining the causes, consequences and repercussions of the climatic and politic events mentioned. They proved to be insufficient to inform and contribute to the formation of local citizens concerned with environmental issues or to help on the creation of regional public policies related to the topic. The reports and press articles concerning the deforestation and forest fires in the Amazon were analyzed through their discourses, taking them as producers of the reality, i.e., the reason for the political struggle for hegemony. The theoretical analysis was based mainly on authors and concepts of Semiology of Social Discourse.
Keywords: Communication; Brazilian Amazon; Environment; Journalistic Sources; Journalistic Discourse; Discursive Formations.